International Audit Differences. Comparison of International Standards on auditing used in EU and Tajikistan´s auditing standards - Ganiev, Manuchehr; Králíček, Vladimír, 1952-; Tyl, Jan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
This thesis is focused on the International Audit standards, as we know, they vary from country to country. The following studies are aimed to analyze international auditing standards used in the Republic of Tajikistan. Main task is to define all differences between audit standards used in the Tajikistan Republic and in European Union and state the reason for them through detailed study. After a detailed study of an audit in the Tajikistan Republic, I will give recommendations, which will help to increase the level of auditing in a country.
Vedoucí práce: Vladimír Králíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses